Details of the Pillars, Pilaster and the small strip of Wall - Temples of India Project Team (Jio Institute, 2024)
Details of the pillars, pilaster and the small strip of wall flanking the principal entrance of the Bhandasar Temple. The small vertical wall space, flanking the entrance, depicts paintings of doorkeepers.